Comparative Study between Bupivacaine with Dexmedetemidine and Bupivacaine with Fentanyl for Caudal Epidural Analgesia Perioperatively in Paediatric Infraumbilical Surgery - Siddique, Md Abu Baker; Ali, Nadeem Parvez; Sarder, Md Atiqul Haque; Rubaiat, Molla Md; Haque, Md Nazmul; Ahmed, Mohammad Nesar Uddin (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Caudal epidural analgesia is a widely used technique to provide intraoperative and postoperative pain relief in paediatric patients undergoing infra-umbilical surgeries. However, a single-dose caudal block with local anaesthetic alone offers only a limited duration of analgesia. To address this, various adjuvants have been combined with local anesthetics to extend analgesic Effects. Although opioids are commonly used as adjuvants, their use is associated with significant adverse Effects, notably respiratory depression. Objective: To compare the efficacy and safety of dexmedetomidine versus fentanyl as adjuvants to bupivacaine in caudal epidural analgesia for paediatric infra-umbilical surgeries. Methods: A total of 45 children (aged 2–7 years, ASA I–II) undergoing elective infra-umbilical surgeries were randomly assigned to two groups of 25 each. Following anaesthesia induction, Group F received 0.25% bupivacaine (0.75 ml/kg) with fentanyl (2 μg/kg) while Group D received 0.25% bupivacaine (0.75 ml/kg) with dexmedetomidine (2 μg/kg) via caudal block. Hemodynamic parameters were monitored regularly. Postoperative pain and sedation were assessed using the FLACC and Ramsay scales, respectively. Time to first rescue analgesia, total 24-hour analgesic use and perioperative complications over six hours were documented. Results: Both paediatric groups (Group F and Group D, n=45) were comparable in demographics, ASA class, surgery type, and anaesthesia duration (p>0.05). Surgical indications were similarly distributed (p=0.762). Heart rate and blood pressures were initially similar but significantly lower in Group D after 10–20 minutes (p<0.05). Group D required fewer intraoperative sedative doses and had higher Ramsay Sedation scores early in the PACU (p<0.05). FLACC scores were mostly similar, except at the 4th PACU hour where Group D had better pain control (p=0.016). Time to first rescue analgesia was longer in Group D (p=0.001), though total 24-hour analgesic use was similar (p=0.458). Adverse events were comparable in both groups (p>0.05). Conclusion: Dexmedetomidine, when used as an adjuvant to bupivacaine in infraumbilical surgeries, provides longer sedation and extended postoperative analgesia compared to fentanyl. It enhances the effect of local anesthetics without increasing side effects. JAFMC Bangladesh, Vol 21, No 2 (December) 2025:29-35